The Loughborough Soccer Passing Test has impractical criterion validity in elite youth football. Issue 1 (2nd January 2017) - Serpiello, F. R.; Cox, A.; Oppici, L.; Hopkins, W. G.; Varley, M. C.
ABSTRACT: Passing ability is of great importance in the development of young football players. The Loughborough Soccer Passing Test (LSPT) was developed to assess short-distance passing ability under time pressure, in a controlled environment. While the test has strong discriminant validity and acceptable test–retest reliability, no information exists on its ability to predict passing performance during a game. The aim of the present study was to assess the criterion validity of the LSPT in elite youth football players. Twenty-four outfield male players from an U18 state-representative team performed the LSPT. Criterion measures of passing performance overall and in high-difficulty scenarios were provided by video analysis of the first eight subsequent games of a competitive season. Validity was quantified as Pearson's correlations between the LSPT score (total and time-only) and the two criterion measures, adjusted for reliability of the criterion measures. The adjusted correlations ranged from 0.30 (90% confidence limits −0.17, 0.74) to 0.47 (−0.02, 0.97), representing impractical to very poor validity. No variable from the game video analysis in isolation (e.g., pass direction, pass location etc.) had a meaningful correlation with the LSPT scores. In conclusion, our results do not support the use of the LSPT as a valid test of in-game passing performance in this cohort of youth players.